Subscription Page (Quarterly Journal of Economics, 2016)
Journal Article Subscription Page Get access The Quarterly Journal of Economics, Volume 131, Issue 2, May 2016, Page i3, https://doi.org/10.1093/qje/qjv050 Published: 19 May 2016